Self-Water-Removal and Voltage Behavior Improvement of Dead-Ended Proton Exchange Membrane Fuel Cell Stack at Steady-State and Dynamic Conditions - Pei, Houchang; Xiao, Chenguang; Xing, Lu; Tu, Zhengkai (Frontiers in Energy Research, 2022)
The proton exchange membrane fuel cell (PEMFC) demonstrates high commercial competitiveness due to its advantages: low operating temperature, high power/mass ratio, fast response, no emission, and low noise. Thermal and water management remains a challenging issue for ensuring the fuel cell's performance at steady-state and dynamic conditions. The cathode moisture condensation uses a semiconductor cooler to effectively remove excess water from the PEMFCs and reduce the probability of flooding of the stack. The stack's voltage uniformity is an essential factor that affects the performance and lifetime of PEMFC. This paper investigates the dynamic response characteristics of the voltage uniformity of a PEMFC stack under cathode moisture condensation conditions. The results show that the condensation temperature at 10℃ during the steady-state or transient operation of the PEMFC can effectively optimize the stack's performance. Compared to conventional PEMFC, applying the cathode moisture condensation technology to the PEMFC stack increases the stack voltage by 6% and decreases the voltage uniformity by up to 30%. This self-water-removal technology effectively improves the voltage uniformity of the stack, which then increase the stack durability.